Incidence of cutoff frequency in nutritional parameters of alfalfa (Medicago sativa L.) of different degrees of winter rest (FAVE Sección Ciencias Veterinarias, 2021)
The objective of this work was to evaluate the nutritional quality in 3 cultivars of alfalfa, belonging to different winter dormancy (GRI), subjected to two cutting frequencies during one year of cultivation, based on the abundant information existing in studies carried out in productivity, coverage and persistence, not so in the determination of quality of forage subjected to different frequencies of cuts and contrasting GRI. Three cultivars (GR6-Verzy), (GR9-Mecha) and (GR10-Ruano) were tested. The experimental design was a complete split plot with four repetitions. Two treatments defined by the cutting intervals were established: T1: 25 days and T2: 35 days. These were specified for spring, summer and fall seasons. For winter the interval was 45 and 55 days in T1 and T2, respectively.  The evaluated variables were: percentage of dry matter (% DM), percentage of crude protein (% PB), percentage of neutral detergent fiber (% FDN) and percentage of acid detergent fiber (% FDA). Significant differences were found for all the nutritional variables studied, for both treatment with p
Keywords: alfalfa; cultivate; nutritional parameters; cutting frequency